Apply the radical rule to separate terms:
Cubicroot(-27) and cubic root(n^27)
Cubicroot(-27) = -3
Now you have -3 cubicroot(n^27)
Using the exponent rule
N^27 can be rewritten as (n^9)^3
Now you have -3 cubicroot((n^9)^3)
The cubic root and the 3rd power cancel out to get the final answer of
-3n^9
Answer:
The correct answer is 6.768.
Step-by-step explanation:
(4.23)(1.6) = 6.768
<span>In 3 years, you will have $8,103.38
Formula:
</span>
<span>A = P (1 + r/n)<span> ^(nt)</span></span>
Where:
A = the future value of the investment/loan, including interest
P = the principal investment amount (the initial deposit or loan amount)
r = the annual interest rate (decimal)
n = the number of times that interest is compounded per year
t = the number of years the money is invested or borrowed for
Answer:
we are looking for F
but in the question it stated that f(n) and at the end it also stated that f(1) so n=1
Step-by-step explanation:
we are using BODMAS
f(n-1)+1
f(1-1)+1=0+1
f=1
Answer:
mi no hablar espanol.
Step-by-step explanation: